A Design and Implementation of a 3-Axis UAV Drone Gimbal Rig for Testing Stability and Performance Parameters in the Laboratory - Wijaya, Ryan Satria; Zulpriadi, Zulpriadi; Prayoga, Senanjung; Fatekha, Rifqi Amalya (Politeknik Negeri Batam, 2025)
This study designs a 3-axis UAV gimbal rig for testing stability and performance before deployment in real-world flight conditions. The gimbal rig simulates the vertical, lateral, and longitudinal axes to ensure reliable operation in various scenarios. Made from lightweight aluminum alloy, the structure minimizes vibrations and maintains rigidity during testing. For precise motion tracking, each axis is equipped with an LPD3806- 600BM-G5 rotary encoder, offering accurate feedback on movement. The Arduino Nano processes the encoder data, displaying real-time results on a 16x2 LCD with an I2C interface for easy monitoring. Additionally, a push-button system enables users to switch between different readings for each axis. This setup aids researchers in analyzing UAV dynamics and refining both firmware and hardware. Future enhancements may include wireless data logging and integration of machine learning techniques to predict maintenance needs, further supporting UAV stability testing in various applications, including aerospace, defense, and commercial use.